The economics of financial and medical identity theft - Camp, L. Jean (Springer US, 2012)
Financial identity theft is well understood with clear underlying motives. Medical identity theft is new and presents a growing problem. The solutions to both problems however, are less clear. The Economics of Financial and Medical Identity Theft discusses how the digital networked environment is critically different from the world of paper, eyeballs and pens. Many of the effective identity protections are embedded behind the eyeballs, where the presumably passive observer is actually a fairly keen student of human behavior. The emergence of medical identity theft and the implications of medical data privacy are described in the second section of this book. The Economics of Financial and Medical Identity Theft also presents an overview of the current technology for identity management. The book closes with a series of vignettes in the last chapter, looking at the risks we may see in the future and how these risks can be mitigated or avoided.